2020
DOI: 10.1186/s12887-020-02166-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department attendance for injury and behaviours suggestive of attention deficit hyperactivity disorder (ADHD): a cross-sectional study

Abstract: Background: The study aimed to investigate if the behaviours suggestive of ADHD were more frequent in a population of children attending the Emergency Department (ED) for injuries, rather than for other causes. Methods: A cross-sectional study was carried out. Patients, aged 6 to 17 years, attending the ED for acute injuries and other causes were considered cases and controls, respectively. We used a questionnaire, which investigates the presence in the child of inattention, hyperactivity, and impulsivity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They found that a higher frequency of ADHD-affected children was prone to multiple body and head injuries (43% and 41%, respectively). Conversano E et al assessed the frequency of admittance to the ER on account of ADHD-related injuries and behavior [ 27 ]. They reported the admittance of 545 such cases, 251 cases with injuries.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a higher frequency of ADHD-affected children was prone to multiple body and head injuries (43% and 41%, respectively). Conversano E et al assessed the frequency of admittance to the ER on account of ADHD-related injuries and behavior [ 27 ]. They reported the admittance of 545 such cases, 251 cases with injuries.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, children and adolescents with ADHD have a higher risk of falls and injury than typically developing children and are therefore more likely to fracture a bone. [13][14][15][16] Although previous studies have demonstrated that the use of methylphenidate is associated with a lower risk of injury, 17,18 given the potential negative bone-metabolic effect of methylphenidate, it is not clear if methylphenidate is associated with the risk of fractures. Fractures have a negative impact on children and young people in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
“…Among the children presenting with injuries, behaviors suggestive of ADHD were found in 22 (%9), while in children with other complaints, 30 (%10) showed behaviors suggestive of ADHD. Indeed, research conducted with children diagnosed with ADHD indicates that they are at a high risk of serious injuries due to increased hyperactivity and decreased attention (Conversano et al 2020). In a qualitative study conducted in Australia, 8 participants were interviewed through semi-structured interviews to explore their perception of ADHD and its diagnosis, as well as their attitudes towards stimulant medication.…”
Section: Introductionmentioning
confidence: 99%